The 2020 Amendments of Russia’s 1993 Constitution: A Post-Colonial Interpretation - Herbert Küpper (Journal of Indonesian Constitutional Law, 2025)
In 2020, Russia enacted far-reaching amendments in its Constitution. The classical theory of democratic constitutionalism sees them as a roll-back into an autocratic and isolationist past the reason of which it cannot explain. The objective of this paper is to give the amendments an additional, post-colonial reading in order to fill the gaps of the classic interpretation. Russia was a colonial power (Tsarist Russia, Soviet Union), lost this status in 1991 and has endeavoured to re-create an empire since 2000. Therefore, it can be analysed with the tools that post-colonial theory has formulated in regard to the former metropolis. This is a new interpretional framework for these constitutional amendments. The method is the legal interpretation of a constitutional text against the background of the post-colonial theory of constitution. This post-colonial interpretation provides a coherent reading of these amendments, showing that Russia wants to re-erect its lost empire. For this purpose, it further centralises all state power in the ‘strong-man president’, stresses Russia’s succession into the imperial tradition of Tsarist Russia and the Soviet Union, and terminates the binding force of international law within Russia. This post-colonial interpretation of the 2020 amendments of the Russian Constitution does not want to replace the conventional interpretation of democratic constitutionalism but gives an additional angle able to fill the gaps that democratic constitutionalism leaves. Furthermore, it contributes to the post-colonial theory of constitutions because it provides a case study of a former metropolis going imperial again.